2021
DOI: 10.1038/s42003-021-01966-w
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenols exert detrimental effects on neuronal signaling in mature vertebrate brains

Abstract: Bisphenols are important plasticizers currently in use and are released at rates of hundreds of tons each year into the biosphere1–3. However, for any bisphenol it is completely unknown if and how it affects the intact adult brain4–6, whose powerful homeostatic mechanisms could potentially compensate any effects bisphenols might have on isolated neurons. Here we analyzed the effects of one month of exposition to BPA or BPS on an identified neuron in the vertebrate brain, using intracellular in vivo recordings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Increases in the caprolactam pathway are interesting because they have been associated with longevity in humans, and high levels of caprolactam metabolising bacteria may provide a protection against toxins in the environment. Environmental toxins such as plastics and synthetic organic compounds have an impact on mental health ( Daniel et al, 2020 ; Minatoya and Kishi, 2021 ; Schirmer et al, 2021 ) and our results raise the possibility that LI-rTMS may facilitate the growth of micro-organisms that can breakdown these compounds, potentially provide a protective effect. It will be important in future studies to determine whether the bacterial changes identified in this study actively contribute to the changes in behaviour, or are merely a consequence of the different interventions.…”
Section: Discussionmentioning
confidence: 70%
“…Increases in the caprolactam pathway are interesting because they have been associated with longevity in humans, and high levels of caprolactam metabolising bacteria may provide a protection against toxins in the environment. Environmental toxins such as plastics and synthetic organic compounds have an impact on mental health ( Daniel et al, 2020 ; Minatoya and Kishi, 2021 ; Schirmer et al, 2021 ) and our results raise the possibility that LI-rTMS may facilitate the growth of micro-organisms that can breakdown these compounds, potentially provide a protective effect. It will be important in future studies to determine whether the bacterial changes identified in this study actively contribute to the changes in behaviour, or are merely a consequence of the different interventions.…”
Section: Discussionmentioning
confidence: 70%
“…Correspondingly, concerns against the use of BPS are rising with the number of studies also revealing detrimental effects of BPS [30,42,49,52,60,61]. Using an in vivo approach, we recently showed that BPA and its main substitute BPS both affect neuronal and synaptic functions in the adult vertebrate brain [54]. Thereby, exposure to small quantities of these plastic compounds over limited time interfered with signal transmission between nerve cells (Figure 2b).…”
Section: Beyond Toxicity Tests: the Blind Spots In Risk Assessmentmentioning
confidence: 99%
“…It affects hormonal balance and reproductive potential and alters neuronal development and metabolic processes in humans, other mammals, birds, and in so-called lower vertebrates [37,[43][44][45][46][47][48][49][50][51][52][53]. Due to its hazardous properties, the scope of application of BPA has been limited in the EU to reduce exposure situations [25] and calls are being made for safer alternatives [54,55]. Although bisphenols also leach into the environment, humans appear to be exposed to bisphenols primarily through food packaging and contaminated food (Figure 2a) [24,38,42,56,57].…”
Section: Beyond Toxicity Tests: the Blind Spots In Risk Assessmentmentioning
confidence: 99%
See 2 more Smart Citations